2014
DOI: 10.1097/md.0000000000000292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Periodontal Therapy on Metabolic Control in Patients With Type 2 Diabetes Mellitus and Periodontal Disease

Abstract: Epidemiologic studies have reported increased incidence, prevalence and acuity of periodontitis in adults with diabetes and some have also suggested that treating periodontal disease may improve glycemic control in diabetic patients.This meta-analysis was conducted to evaluate the effects of different periodontal therapies on metabolic control in patients with type 2 diabetes mellitus (T2DM) and periodontal disease.We searched the Medline, EMBASE and Cochrane Library (Central) databases up to January 2014 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 31 publications
3
67
1
3
Order By: Relevance
“…oral taxon 041 HOT 041, and Synergistetes [28][29][30][31]. Recent studies have indicated that periodontal disease and systemic health are closely linked and treating periodontal disease may help with the prevention of several other chronic inflammatory conditions, including IgAN [6,[16][17][18][19]25]. IgAN is the most common primary glomerulonephritis wherein immune complexes consisting of IgA1 with galactose-deficient hinge region and anti-glycan antibodies deposit in glomeruli and induce renal injury [32].…”
Section: Discussionmentioning
confidence: 99%
“…oral taxon 041 HOT 041, and Synergistetes [28][29][30][31]. Recent studies have indicated that periodontal disease and systemic health are closely linked and treating periodontal disease may help with the prevention of several other chronic inflammatory conditions, including IgAN [6,[16][17][18][19]25]. IgAN is the most common primary glomerulonephritis wherein immune complexes consisting of IgA1 with galactose-deficient hinge region and anti-glycan antibodies deposit in glomeruli and induce renal injury [32].…”
Section: Discussionmentioning
confidence: 99%
“…& Chronic periodontal inflammation may increase the risk for type 2 diabetes [41••, 42-46, 47•]. & Although the predominance of evidence suggests that treatment of periodontal disease may improve glycemic control, this is inconclusive [48][49][50][51][52][53][54][55][56][57]. However, a recent Cochrane Review concluded that there is insufficient evidence that improvement in glycemic control can be maintained after 4 months following treatment using nonsurgical treatment modalities [58•].…”
Section: Evidence On the Interrelationship Between Diabetes And Periomentioning
confidence: 98%
“…Dessa forma o grupo de diabéti-cos mal controlados apresentou aumento do percentual de cálculo e maior risco de periodontite1. 12,[13][14][15] Awartani pesquisou a influência dos níveis séricos de imunoglobulinas (IgA, IgG, IgM) em diabéticos tipo 2 (mal controlados e bem controlados) e não diabéticos com periodontite crônica.12 Os pacientes foram divididos em três grupos. O Grupo 1 foi formado por diabéti-cos que exibem um melhor controle glicêmico e o Grupo 2 por diabéticos com mau controle.…”
Section: -11unclassified